Spatiotemporal variability in fire foci detection in the state of Pará, Brazil - Benjamin Leonardo Alves WHITE (Acta Amazonica, 2024)
ABSTRACT In the current climate change scenario, the adoption of actions aimed at reducing wildland fires and, consequently, greenhouse gas emissions is urgent. The use of environmental satellites to trace wildland fires is an essential instrument in the development of fire prevention strategies. The objectives of this study were to (a) analyze the spatiotemporal variability in fire foci detection in the state of Pará, Brazil; (b) identify the main differences between data from AQUA and Suomi-NPP (S-NPP) satellites; and (c) determine the variables responsible for changes in fire detection at municipal level. Mean annual detection of fire foci was of 43,488 by AQUA based on data from 2003-2023, and of 156,038 by S-NPP from 2012-2023. During the overlap period, S-NPP detected 4.5 times more foci than AQUA. Despite the difference, both datasets were significantly correlated. Most fire foci were detected in August, September and November. São Félix do Xingu and Altamira were the municipalities with the highest number of detections, while Bajaru and Concórdia do Pará registered higher fire foci density. Of the 144 municipalities, 89 were classified as having extreme fire incidence. Deforested area was the variable that presented the highest correlation with municipal fire density, followed by pasture area, rainfall, urbanized area, forest area, agricultural area and demographic density. The results of this study could be used as basis for the development of public policies aiming at the reduction of wildland fire occurrence in Pará.